Commonsense reasoning - Mueller, Erik T. (Amsterdam ; Boston : Elsevier Morgan Kaufmann, 2006)
To endow computers with common sense is one of the major long-term goals of Artificial Intelligence research. One approach to this problem is to formalize commonsense reasoning using mathematical logic. Commonsense Reasoning is a detailed, high-level reference on logic-based commonsense reasoning. It uses the event calculus, a highly powerful and usable tool for commonsense reasoning, which Erik T. Mueller demonstrates as the most effective tool for the broadest range of applications. He provides an up-to-date work promoting the use of the event calculus for commonsense reasoning, and bringing into one place information scattered across many books and papers. Mueller shares the knowledge gained in using the event calculus and extends the literature with detailed event calculus solutions to problems that span many areas of the commonsense world. Covers key areas of commonsense reasoning including action, change, defaults, space, and mental states. The first full book on commonsense reasoning to use the event calculus. Contextualizes the event calculus within the framework of commonsense reasoning, introducing the event calculus as the best method overall. Focuses on how to use the event calculus formalism to perform commonsense reasoning, while existing papers and books examine the formalisms themselves. Includes fully worked out proofs and circumscriptions for every example. Describes software tools that can be downloaded and used for automated commonsense reasoning, and real-world applications that have been built using the event calculus.
Chapter 1: Introduction -- 1.1 What is Commonsense Reasoning? -- 1.2 Key Issues of Commonsense Reasoning -- 1.3 Brief History of Commonsense Reasoning -- 1.4 The Event Calculus -- Part I: Foundations -- Chapter 2: The Event Calculus -- 2.1 First-Order Logic -- 2.2 Event Calculus Basics -- 2.3 Event Calculus Axiomatizations -- 2.4 Reification -- 2.5 Conditions -- 2.6 Circumscription -- 2.7 Domain Descriptions -- 2.8 Reasoning Types -- -- Part II: Commonsense Phenomena -- Chapter 3: The Effects of Events -- 3.1 Positive and Negative Effect Axioms -- 3.2 Effect Axiom Idioms -- 3.3 Preconditions -- 3.4 State Constraints -- -- Chapter 4: The Triggering of Events -- 4.1 Trigger Axioms -- 4.2 Preventing Repeated Triggering -- 4.3 Triggered Fluents -- -- Chapter 5: The Commonsense Law of Inertia -- 5.1 Representation of the Commonsense Law of Inertia -- 5.2 Representing Release from the Commonsense Law of Inertia -- 5.3 Release Axioms -- Chapter 6: Indirect Effects of Events -- 6.1 Effect Axioms -- 6.2 Primitive and Derived Fluents -- 6.3 Release Axioms and State Constraints -- 6.4 Effect Constraints -- 6.5 Causal Constraints -- 6.6 Trigger Axioms -- Chapter 7: Continuous Change -- 7.1 Trajectory Axioms -- 7.2 AntiTrajectory Axioms -- 7.3 Using AntiTrajectory Instead of Releases -- Chapter 8: Concurrent Events -- 8.1 Restricting Concurrency -- 8.2 Cumulative and Canceling Effects -- Chapter 9: Nondeterministic Effects of Events -- 9.1 Determining Fluents -- 9.2 Disjunctive Event Axioms -- Part III: Commonsense Domains -- Chapter 10: Space -- 10.1 Relational Space -- 10.2 Metric Space -- 10.3 Object Identity -- Chapter 11: The Mental States of Agents -- 11.1 Beliefs, Goals, and Plans -- 11.2 Emotions -- -- Part IV: Default Reasoning -- Chapter 12: Default Reasoning -- 12.1 Atemporal Default Reasoning -- 12.2 Temporal Default Reasoning -- 12.3 Default Reasoning Method -- 12.4 Defaults and the Qualification Problem -- 12.5 Default Events and Properties -- Part V: Programs and Applications -- Chapter 13: The Discrete Event Calculus Reasoner -- 13.1 Discrete Event Calculus Reasoner Architecture -- 13.2 Encoding SAT Problems -- 13.3 Simple Examples -- 13.4 Example: Telephone -- 13.5 Discrete Event Calculus Reasoner Language -- Chapter 14: Applications -- 14.1 Business Systems -- 14.2 Natural Language Understanding -- 14.3 Vision -- Part VI: Logical and Nonlogical Methods -- Chapter 15: Logics for Commonsense Reasoning -- 15.1 Situation Calculus -- 15.2 Features and Fluents -- 15.3 Action Languages -- 15.4 Fluent Calculus -- 15.5 Discussion and Summary -- -- Chapter 16: Nonlogical Methods for Commonsense Reasoning -- 16.1 Qualitative Reasoning -- 16.2 Analogical Processing -- 16.3 Probabilistic Reasoning -- 16.4 Society of Mind -- Part VII: Conclusion -- Chapter 17: Conclusion -- Part VIII: Appendices -- Appendix A: Logical Foundations -- Appendix B: Equivalence of EC and DEC -- Appendix C: Events with Duration -- Appendix D: Answers to Selected Exercises.
Includes bibliographical references (p. 361-390) and index.
Keywords: Commonsense reasoning -- Automation; Artificial intelligence -- Mathematics; Logic, Symbolic and mathematical -- Data processing; Electronic books